Settlement Through Mediation Between the Normative and Practice in Religious Judiciary Agencies - Karmawan, Karmawan; Abdillah, Masykuri (Jurnal Cita Hukum, 2020)
Abstract:Mediation in religious courts is believed to be an effective mechanism for reducing the case buildup. Due to the completion of the case at the mediation stage, the parties do not need to continue the litigation process. The agreement reached in the mediation process will be ratified by the judge and therefore has the same legal consequences as the judge's decision. Normatively mediation based on PerMA Number 1 of 2016 provides a new direction as the Supreme Court's policy to put more pressure on the number of cases that enter the court so that mediation at the court level will reduce the accumulation of cases. Even the practices of mediation at the religious court level mediators still use traditional methods like advising the parties. As the court case is examined, the parties to the dispute can see that litigation no longer provides a better solution.Keywords: Mediation, mediator, normative, practice, the religious court Abstrak:Mediasi di pengadilan agama diyakini sebagai mekanisme yang efektif untuk mengurangi penumpukan kasus. Karena penyelesaian kasus pada tahap mediasi, para pihak tidak perlu melanjutkan proses litigasi. Kesepakatan yang dicapai dalam proses mediasi akan disahkan oleh hakim dan karenanya memiliki konsekuensi hukum yang sama dengan keputusan hakim. Mediasi secara normal berdasarkan PerMA Nomor 1 tahun 2016 memberikan arah baru karena kebijakan Mahkamah Agung untuk lebih menekan jumlah kasus yang masuk ke pengadilan sehingga mediasi di tingkat pengadilan akan mengurangi akumulasi kasus. Bahkan praktik-praktik mediasi di tingkat pengadilan religius mediator masih menggunakan metode tradisional seperti menasihati para pihak. Ketika kasus pengadilan diperiksa, adalah mungkin bagi para pihak yang berselisih untuk melihat bahwa proses pengadilan tidak lagi memberikan solusi yang lebih baik.Kata kunci: Mediasi, mediator, normatif, praktik, pengadilan agama Аннотация:Посредничество в религиозных судах, как полагают, является эффективным механизмом для уменьшения количества дел. В связи с завершением дела на стадии посредничества сторонам не нужно продолжать судебный процесс. Соглашение, достигнутое в процессе посредничества, будет ратифицировано судьей и, следовательно, имеет те же правовые последствия, что и решение судьи. Нормативно, посредничество, основанное на Правилах Верховного Суда (PerMA) № 1 от 2016 года, обеспечивает новое направление политики Верховного суда, направленное на подавление количества дел, поступающих в суд, с тем, чтобы посредничество на уровне суда снизило их совокупность. Однако практика посредничества на уровне религиозного суда показывает, что посредник все еще использует традиционные методы, такие как консультирование сторон. Поскольку судебное дело рассматривается, стороны в споре могут увидеть, что судебный процесс больше не дает лучшего решения.Ключевые слова: Посредничество, Посредник, Норматив, Практика, Религиозный суд